2023
DOI: 10.1136/bmjgh-2023-012042
|View full text |Cite
|
Sign up to set email alerts
|

Health taxes in Indonesia: a review of policy debates on the tobacco, alcoholic beverages and sugar-sweetened beverage taxes in the media

Abdillah Ahsan,
Nadira Amalia,
Krisna Puji Rahmayanti
et al.

Abstract: IntroductionOne of the WHO’s ‘best buys’ in controlling non-communicable diseases and their risk factors is to impose health taxes. While the Indonesian political process inhibits the implementation of health tax policy, studies to discuss the issue remain limited.MethodsWe employed media analysis to document health tax policy dynamics, for example, the changes in policy timeline and key actors’ statements. We conducted an article search in the Open-Source Intelligence database using appropriate terminology on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
(101 reference statements)
0
6
0
Order By: Relevance
“…In Indonesia, Ahsan et al conducted a review of media policy debates on the tobacco, alcoholic beverages and SSBs taxes. 30 They found that while tobacco tax policy has changed significantly, there has been little policy movement on alcohol and SSB taxes. 30 Leading up to the elections of 2019, media framing intensified, with many political figures adopting clear positions in opposition to taxation.…”
Section: Lessons From Individual Case Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…In Indonesia, Ahsan et al conducted a review of media policy debates on the tobacco, alcoholic beverages and SSBs taxes. 30 They found that while tobacco tax policy has changed significantly, there has been little policy movement on alcohol and SSB taxes. 30 Leading up to the elections of 2019, media framing intensified, with many political figures adopting clear positions in opposition to taxation.…”
Section: Lessons From Individual Case Studiesmentioning
confidence: 99%
“… 30 They found that while tobacco tax policy has changed significantly, there has been little policy movement on alcohol and SSB taxes. 30 Leading up to the elections of 2019, media framing intensified, with many political figures adopting clear positions in opposition to taxation. 30 Policy debates on tobacco and e-cigarette taxation in Indonesia prioritised economic interests over health interests.…”
Section: Lessons From Individual Case Studiesmentioning
confidence: 99%
See 3 more Smart Citations